2013
DOI: 10.5489/cuaj.205
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antibiotic Prophylaxis Prescribing Patterns for TURP: A Need for Canadian Guidelines?

Abstract: Background: While antibiotic prophylaxis is recommended to all patients undergoing transurethral resection of prostate (TURP), little data exist regarding prescribing patterns of urologists prior to this procedure. Here, we sought to determine real-world antibiotic prophylaxis prescribing patterns at a high volume Canadian institution and determine compliance rates to recommendations put forth by the American Urological Association's (AUA) Best Practice Statement (BPS) on antimicrobial prophylaxis. Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Also, there is no consensus regarding the use of antibiotics; Lawson et al noticed in a review of 488 patients who underwent TURP that a total of 30 antibiotic regimens were utilised. The most common single antibiotic regimens prescribed were ciprofloxacin (32%), cefazolin (25%), and gentamicin (3%) [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, there is no consensus regarding the use of antibiotics; Lawson et al noticed in a review of 488 patients who underwent TURP that a total of 30 antibiotic regimens were utilised. The most common single antibiotic regimens prescribed were ciprofloxacin (32%), cefazolin (25%), and gentamicin (3%) [5].…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to said data, the present study only surveyed 3 diabetic patients with a postoperative positive urine culture [18]. All guidelines recommend the administration of antibiotic prophylaxis in men who will undergo TUR-P to reduce the risk of UTIs or asymptomatic bacteriuria [5,19]. Many studies are evaluating the effects of antibiotic prophylaxis on men undergoing TURP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing TURP with a foley catheter in place can increase the risk of infection. The use of gentamicin in these patients shows a reasonably stable condition and reduces infection risk (Lawson, Rudzinski, Vicas & Carlson, 2013).…”
Section: Prophylactic Antibiotic Therapy In Bph Patientsmentioning
confidence: 87%
“…1 Overall, 488 patients are grouped into two distinct sets: A set with an indwelling catheter and the other with no preoperative catheter. It is shown that the compliance rate with the AUA best practice statement (BPS) (which recommended antibiotic prophylaxis in all TURP patients) is 81% in the first set of patients and 37% in the second.…”
mentioning
confidence: 99%